Exploring work-family balance perception in creative industry - Aziz, Azelin; Ahmad, Mohd Khairie (Faculty of Computing, Universiti Teknologi Malaysia, 2016)
Previous research suggests that employees in the creative industry are likely to hold several jobs, working irregular time, employment are short-term, with little career security and uncertain job prospects, and nevertheless the workforce appears to be growing.As Creative Industry has been projected to be one of the Malaysia economic sources, it is critical to understand the working-life quality on this highly increasing industry. This study explores how Malaysian creative industries’ related workers view a balanced work-family life. Series of in-depth interviews were conducted on 12 creative industry workers. Data were transcribed and analyse using thematic analysis methods.The results suggest that work-family balance was viewed from several perspectives – role participation, role conflict, and role achievement.